Dietary Pattern for Helicobacter pylori Eradication - Zam, Wissam (Natural Products Journal, The, 2018)
Helicobacter pylori are a widespread chronic infection that accompanied man from long ago. The infection is responsible for the majority of peptic ulcer, stomach cancer and dyspeptic symptoms. Large-scale eradication therapy regimens are linked with a rapid increase in antibiotic resistance. Moreover, different regimens used for therapy require multiple-day complex drug administration and are associated with side effects which can lead to treatment discontinuation. Our diet contains many substances with proven bacteriostatic or bactericidal properties against H. pylori. Although these food products are not proven to allow permanent H. pylori eradication, they can reduce bacterial colonization, the degree of stomach inflammation, thus potentially lowering the risk of gastric adenocarcinoma development.
Keywords: in vitro studies